Demonstration of a Hybrid B5G System Integrating VLC and RF-Based Technologies with Access Networks - Tomás Powell Villena Andrade; Celso Henrique de Souza Lopes; Letícia Carneiro de Souza; Arismar Cerqueira Sodré Junior (Applied Sciences)
Visible-light communication (VLC) has emerged as a promising technology to provide the very high-throughput wireless communications demanded by beyond-fifth-generation (B5G) applications. However, few works are found in the literature regarding the integration of VLC systems with other wireless communications technologies and with access networks. In this context, and as a proof of concept, we implement and experimentally evaluate a hybrid network architecture based on VLC, radio-over-fiber (RoF), free space optics (FSO), fiber-wireless (FiWi), and millimeter-waves (mm-waves) for B5G applications. Such optical networks make use of fiber-optic links based on RoF technology as backhauls, whereas their fronthauls might be either by FSO or RoF. Finally, a triple-wireless-access network is ensured by VLC, FiWi, and mm-wave links. The latter use a real 5G new radio (5G NR) signal. The system performance is evaluated in terms of a root mean square error vector magnitude (EVMRMS) parameter in accordance with the 3rd-Generation Partnership Project (3GPP) requirements. The experimental results demonstrate a total maximal theoretical throughput of approximately 1.66 Gbps, aligning with the digital performance requirements set by 3GPP.